2018
DOI: 10.1111/ijfs.13929
|View full text |Cite
|
Sign up to set email alerts
|

Tannase improves gallic acid bioaccessibility and maintains the quality of mango juice

Abstract: The effect of tannase on gallic acid (GA) bioaccessibility and auto-oxidative browning of mango juice was investigated. After 2 h of simulated gastric digestion, the concentration of bioaccessible GA increased (P < 0.05) 94.3 AE 7.0% in juice treated with 0.5 U mL À1 tannase while juice not treated with tannase had only a 6.3 AE 3.4% increase in GA. During 2-10 h of simulated intestinal digestion, tannase treated juice continued to have a higher concentration (P < 0.05) of bioaccessible GA in comparison to jui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Sirven et al . demonstrated the effect of tannase, an inducible enzyme, on gallic acid bioaccessibility and the prevention of browning through oxidation processes in mango ( Margifera indica ) juice. A higher level of gallic acid bioaccessibility in juice pretreated with tannase was demonstrated by in vitro digestion.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Sirven et al . demonstrated the effect of tannase, an inducible enzyme, on gallic acid bioaccessibility and the prevention of browning through oxidation processes in mango ( Margifera indica ) juice. A higher level of gallic acid bioaccessibility in juice pretreated with tannase was demonstrated by in vitro digestion.…”
supporting
confidence: 88%
“…A higher level of gallic acid bioaccessibility in juice pretreated with tannase was demonstrated by in vitro digestion. This study concluded that an improvement in bioaccessibility of mango polyphenols could be enhanced without significant effects on the quality of mango juice during storage (Sirven, Negrete et al . 2019).…”
mentioning
confidence: 99%
“…The resulting concentration of the tannic acid isolate was 11 423 mg L −1 gallic acid equivalents. To confirm the purity of GT, the extract was analyzed using a Thermo‐Finnigan Surveyor high‐performance liquid chromatography‐photodiode array detector (HPLC‐PDA) in tandem with a LCQ Deca XP Max ion trap spectrometer with an ESI source as previously described . GTs and their derivatives were characterized at 280 nm.…”
Section: Methodsmentioning
confidence: 99%
“…HTs contains mainly glucogallin, gallotannins, ellagitannins, and their derivatives (39). Tannase (a glycoprotein esterase) hydrolyzes GA from gallotannins, thereby increasing available GA absorbed in the gastrointestinal tract (GIT) (40,41). The GA groups are usually bonded to form dimers, such as ellagic acid.…”
Section: Physicochemical Properties Of Gamentioning
confidence: 99%
“…GA liposomes decorated with lactoferrin (LF-GA-LIP) could be developed as a favorable delivery system because it displayed a delayed-release effect in simulated digestion ( 73 ). Recent studies reported that the addition of tannase could enhance GA bioaccessibility in green tea and mango juice ( 40 , 41 ). Repeated dosing and the use of structural analogs or derivative compounds of GA also were effective measures to improve the plasma levels of GA ( 3 ).…”
Section: Bioavailability Absorption and Metabolism Of Gamentioning
confidence: 99%